2013
DOI: 10.1371/journal.pone.0081884
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CHIP as a Novel Causative Gene for Autosomal Recessive Cerebellar Ataxia

Abstract: Autosomal recessive cerebellar ataxias are a group of neurodegenerative disorders that are characterized by complex clinical and genetic heterogeneity. Although more than 20 disease-causing genes have been identified, many patients are still currently without a molecular diagnosis. In a two-generation autosomal recessive cerebellar ataxia family, we mapped a linkage to a minimal candidate region on chromosome 16p13.3 flanked by single-nucleotide polymorphism markers rs11248850 and rs1218762. By combining the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 44 publications
4
100
1
Order By: Relevance
“…Clinical pyramidal tract signs in the absence of electrophysiogical evidence of pyramidal damage (as observed in 25130_01 and his brother) is a feature commonly seen in hereditary spastic paraplegias [13], and most likely explained by predominantly axonal damage of the corticospinal tracts in these subjects [13]. Pyramidal tract signs were also observed in several of the previously reported STUB1 families [4,5]. In sum, this frequent combination of ataxia with pyramidal tract damage indicates that STUB1 ataxia should be added to the differential diagnosis of the rapidly increasing list of “spastic ataxia” spectrum disorders [14].…”
Section: Discussionmentioning
confidence: 72%
“…Clinical pyramidal tract signs in the absence of electrophysiogical evidence of pyramidal damage (as observed in 25130_01 and his brother) is a feature commonly seen in hereditary spastic paraplegias [13], and most likely explained by predominantly axonal damage of the corticospinal tracts in these subjects [13]. Pyramidal tract signs were also observed in several of the previously reported STUB1 families [4,5]. In sum, this frequent combination of ataxia with pyramidal tract damage indicates that STUB1 ataxia should be added to the differential diagnosis of the rapidly increasing list of “spastic ataxia” spectrum disorders [14].…”
Section: Discussionmentioning
confidence: 72%
“…CHIP plays a crucial role in cytoplasmic homeostasis and cell viability by decreasing or stabilizing its substrates [11,12] . It participates in a number of biological processes, especially in neurodegeneration including AD, PD, HD, ALS, and several types of ataxia [12,13,[24][25][26][27][28] . Here, we showed that the clearance occurs frequently in neurodegenerative diseases [3,4] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CHIP has protective effects against the toxicity of neurodegenerative disease proteins. Recently, loss-of-function mutations in CHIP were identified as a causative genetic factor for a group of autosomal recessive cerebellar ataxias [24][25][26][27][28] . However, the precise mechanism of the involvement of CHIP in neurodegeneration remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in TMEM240 (SCA21) [11] and NOL3 [12] have been described in complex phenotypes. In AR-HCAs (SCAR16), STUB1 mutations were described in three kindred with early-onset ataxia [13], and one family with ataxia and hypogonadism [14]. STUB1 was subsequently implicated in later-onset ataxia, with associated pyramidal tract damage [15].…”
Section: A Bumper Harvest Of Novel Genesmentioning
confidence: 99%
“…Involvement of GRID2, encoding the glutamate receptor q2 protein (GluRD2), which belongs to the family of ionotropic glutamate receptors, has already been mentioned above. STUB1-encoded protein has been shown, in combination with Fbx2, to promote the ubiquitination and subsequent degradation of the NR2A subunit of N-methyl-D-aspartate receptors [82], an ability that was impaired in the mutant proteins [13]. SPTBN2 protein product, whose mutations account for SCA5, stabilises the glutamate transporter EAAT4 at the cell membrane [83]; in SCA5 cerebellum extracts, EAAT4 levels were decreased, as was previously reported in SCA23 [84], and in SCA1 transgenic mouse [85].…”
Section: Glutamate Transmissionmentioning
confidence: 99%